Postnational constitutionalism : Europe and the time of law - Linden-Retek, Paul (Oxford studies in European law., 2023)
"At a time when the project of integrating Europe's peoples through the rule of law is faltering, this book develops a critical theory of postnational constitutionalism. Today, widely held conceptions of European law continue to mislead citizens about the nature of political identity, sovereignty, and agency. They lose sight of a critical idea on which postnationalism depends: that constitutional self-authorship is a narrative affair and the polity is a subject whose identity, history, and legacy are still in formation. Absent this vision, European law reproduces crises of legitimacy: the depoliticization of public life; emergency rule by executive decree; a collapse of solidarity; and the rise of nativist movements. The book diagnoses this impasse as the product of a problem familiar to modernity: reification—a process in which social and historical relationships are misattributed as timeless relations among things. Reification's shrinking of social dilemmas, moral principles, and political action to narrow perceptions of the present explains law's role in perpetuating crisis. But this diagnosis also points to a remedy. It suggests that to sustain the emancipatory potential of European constitutionalism we must recover the time of law. The book offers a more temporally attuned constitutional theory with the principles of anti-reification, narrative interpretation, and non-sovereign agency at its centre. These principles reimagine essential domains of constitutional order: social integration, constitutional adjudication, and constituent power. Spanning various bodies of European jurisprudence, the book devotes particular attention to migration and asylum, struggles where questions of solidarity, law, and belonging are most acute and generative"--Publisher's description.